Simulation-based Learning Experiences in Stuttering Management Delivered Online: What Do Students, Clinical Educators and Simulated Patients Think? - Penman, Adriana; Waite, Monique; Hill, Anne E.; Leslie, Taliesha-jayne; Whelan, Brooke-Mai; Whitehead, Andrea (International Journal of Practice-based Learning in Health and Social Care, 2022)
<span class="NormalTextRun SCXW97826046 BCX9" data-ccp-parastyle="Abstract" data-ccp-parastyle-defn="{"ObjectId":"84d0a209-ecc2-49f1-9cd8-a2500e1dcfe6|198","ClassId":1073872969,"Properties":[469775450,"Abstract",201340122,"2",134234082,"true",134233614,"true",469778129,"Abstract",335572020,"1",469777841,"Times New Roman",469777842,"Arial",469777843,"Times New Roman",469777844,"Times New Roman",469769226,"Times New Roman,Arial",268442635,"20",335559685,"709",335559737,"425",335559740,"240",201341983,"0",335559739,"200",335551550,"6",335551620,"6",469777929,"Abstract Char",469775498,"Keywords",469778324,"Normal",469778325,"[\"Comments\"]"]}" data-ccp-parastyle-linked-defn="{"ObjectId":"84d0a209-ecc2-49f1-9cd8-a2500e1dcfe6|235","ClassId":1073872969,"Properties":[469775450,"Abstract Char",201340122,"1",134233614,"true",469778129,"AbstractChar",335572020,"1",134231262,"true",469777841,"Times New Roman",469777842,"Arial",469777843,"Times New Roman",469777844,"Times New Roman",469769226,"Times New Roman,Arial",469777929,"Abstract",469778324,"Default Paragraph Font",469778325,"[\"Comments Char\"]"]}">Speech pathology students are required to demonstrate competency across a range of practice areas. There are, however, limited opportunities for students to access clinical placements in the area of stuttering. Simulation-based learning (SBL) activities have proven to be effective in increasing students’ clinical experience in this area. Due to the COVID-19 pandemic, the delivery of in-person SBL programs was not feasible, resulting in a shift to online provision. The aim of this study was to investigate the perceptions of students, clinical educators and simulated patients who participated in an online adult stuttering SBL experience. Ten first-year graduate entry Masters program speech pathology students participated in the study alongside four clinical educators and four simulated patients. The experience involved two online SBL sessions and one online tutorial via videoconferencing from separate locations. Each participant group engaged in focus group interviews exploring their perceptions of the online SBL activity. Thematic network analysis of the focus group interview data was conducted. Overall interpretation of the data from the perspectives of students, clinical educators and simulated patients revealed an overarching global theme that online SBL offers a positive, comfortable and comparable experience to enable students to build client-centred, clinical and telepractice skills. The positive outcomes of this study suggest that together with in-person clinical experiences, online SBL has an important role in the education of speech pathology students.